A continent for commerce. Issue 1 (12th January 2015) - Cole, Graham
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds impartial comments and places the articles in context. Findings – Up until recently, you would struggle to hear anyone mentioning business success and African firms in the same sentence. Barriers at institutional, sector and company levels saw to by ensuring performance was invariably below standard. How things have changed. Africa's economy is expanding fast and its enterprises are becoming ever more competitive. Firms, entrepreneurships and private sector development are all rising in number. Several leading economic institutes are, on record, anticipating an increasingly significant contribution for African commerce on the global stage. The situation has even been compared with the meteoric economic transformation in Asia. Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best and most pertinent information, and by presenting it in a condensed and easy-to-digest format.